2019
DOI: 10.1111/tct.13091
|View full text |Cite
|
Sign up to set email alerts
|

A flipped classroom in graduate medical education

Abstract: Summary Background The role of the flipped classroom model in graduate medical education (GME) is not yet defined. We set out to evaluate the feasibility, acceptability and outcomes of a flipped classroom instructional model in an internal medicine curriculum. Methods This pilot study was carried out in an academic medical centre in the USA with 43 second‐year internal medicine postgraduate trainees. Trainees watched videos on the pharmacological treatment of type 2 diabetes outside of the classroom, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 12 publications
1
41
0
4
Order By: Relevance
“…Some GME programs have reported success using short videos to help achieve procedural readiness [19][20] , and others have successfully implemented flipped classroom activities using online videos. [21][22] In the context of flipped classroom learning activities, a video pencast curriculum could easily serve as the preparatory material to be viewed prior to casebased active learning sessions. The effects of flipped classroom teaching on learning outcomes in GME has been mixed, despite high levels of resident satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some GME programs have reported success using short videos to help achieve procedural readiness [19][20] , and others have successfully implemented flipped classroom activities using online videos. [21][22] In the context of flipped classroom learning activities, a video pencast curriculum could easily serve as the preparatory material to be viewed prior to casebased active learning sessions. The effects of flipped classroom teaching on learning outcomes in GME has been mixed, despite high levels of resident satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of flipped classroom teaching on learning outcomes in GME has been mixed, despite high levels of resident satisfaction. [21][22][23][24] Recent work by Graham et al. describes successful implementation and improved long-term knowledge outcomes with a flipped classroom for internal medicine residents on an ambulatory rotation.…”
Section: Discussionmentioning
confidence: 99%
“… Method of evaluation Did the study discuss instrument reliability, standardization, and/or validity if utilized? [ 86 ] Physiotherapy students (3rd year) To teach ethics in physiotherapy Blended learning Spain Effectiveness; satisfaction No Self-reported questionnaires (the Attitudes Questionnaire towards Professional Ethics in Physiotherapy – AQPEPT; Perceptions about Knowledge regarding Professional Ethics in Physiotherapy; and a student’s opinion questionnaire The self-reported questionnaire were previously validated with good-high reliability (Cronbach’s alpha = 0.898; 0.760 respectively); the reliability/standardization/validity of the student’s opinion questionnaire was Not indicated [ 103 ] Medical students (6th year); practicing family doctors and interns To improve professional competence in the certification of causes of death in the Spanish National Health System Blended learning Spain Effectiveness; satisfaction No “Quasi-experimental” pre- and post-survey Not indicated [ 104 ] Internal medicine postgraduate trainees (2nd year) To teach outpatient diabetes management Flipped classroom USA Effectiveness; efficiency; satisfaction No Opinion questionnaire; focus groups; pre-post and 6 month follow-up knowledge test (New England Journal of Medicine Knowledge + Question Bank); and an attitudinal survey using a 5-point Likert scale Not indicated for the opinion questionnaire and the attitudinal survey; the Knowledge + Question Bank seems to be standardized [ 105 ] All dental students (year not specified) registered in a Clerkship at the Department of Oral and Maxillofacial Surgery To teach material on oral and maxillofacial surgery in a 2-week clerkship Blended learning using a flipped classroom approach Germany Effectiveness; efficiency; satisfaction No Pre-post test ...…”
Section: Resultsmentioning
confidence: 99%
“…In a cohort of PGY-3 pediatric emergency medicine residents, an FC model combined with interactive application-style questions led to improved scores on core pediatric emergency medicine topics [12]. Blair et al did pre-tests and post-tests followed by a six-month follow-up test and found an improvement after their FC trial in internal medicine residents; however, there was no control group [13]. In similar fashion to the FC model, supplemental videos made available to otolaryngology residents but not scheduled in the curriculum and not made part of an FC paradigm led to improved scores on junior residents' otolaryngology in-training examinations in the pediatric otolaryngology, otology, and facial plastic surgery sections [14].…”
Section: Discussionmentioning
confidence: 99%